Wellens’ Syndrome, a case report of an electrocardiographic warning sign - Sedhai, Yub Raj; Pawar, Aditya Singh; Bhattacharya, Priyanka T.; Basnyat, Soney (Journal of Advances in Internal Medicine, 2017)
Introduction Wellens’ syndrome is described as a characteristic biphasic or symmetrical electrocardiographic T-wave inversions in precordial leads seen in a subset of patients with unstable angina. It is associated with critical stenosis of left anterior descending coronary artery. These patients have a high likelihood of progressing to acute myocardial infarction within a few days to weeks of onset of symptoms, thus it warrants an early invasive approach. Case Presentation: We present a 33-year-old otherwise healthy Indo-Jamaican male who presented with chest pain and characteristic electrocardiographic changes. Wellens’ syndrome was recognized. Emergent coronary angiography revealed 99% stenosis of proximal left anterior descending coronary artery. It was treated with a drug eluting stent. Conclusion: Electrocardiographic changes in Wellens’ syndrome are subtle and characteristically appear during chest pain free interval. It can be easily overlooked as non-specific ST, T wave change. Clinicians should be well aware of this subtle yet alarming electrocardiographic sign. This case report underlines the importance of recognizing the ominous electrocardiographic sign and its association with critical stenosis of the left anterior descending coronary artery. Journal of Advances in Internal Medicine 2016;05(01):19-23